Architectural environment modification for alleviation of allergic sensitization to air pollutants in the urban indoor environment - Tiotuico, Elke Simone F. (Muhon : Journal of Architecture, Landscape Architecture, and the Designed Environment, 2022)
Access online through this link: https://journals.upd.edu.ph/index.php/muhon/article/view/8890/7814